Modeling a Discrete Wet-Dry Algorithm for Hurricane Storm Surge in Alloy - Baugh, John; Altuntas, Alper (Abstract State Machines, Alloy, B, TLA, VDM, and Z, 2016)
We describe an Alloy model that helps check the correctness of a discrete wet-dry algorithm used in a system for hurricane storm surge prediction. Derived from simplified physics and encoded with empirical rules, the algorithm operates on a finite element mesh to allow the propagation of overland flows. Our study is motivated by complex interactions between the algorithm and a recent performance enhancement to the system that involves mesh partitioning. We briefly outline our approach and describe safety properties of the extension, as well as directions for future work.